Engineering physics - Mukherji, Uma (Alpha Science International, 2007)
This text covers topics which are still at research level, such as holography, production of three-dimensional photographs, superconductivity, fibre optics, and communications. Each chapter is accompanied by problems and question papers. This edition provides seven new topics.